3D seismic prediction of low rank coalbed methane enrichment area in the southern margin of Junggar Basin - Xu Maoxuan; Du Wenfeng; He Yunlan; Yang Feng (矿业科学学报, 2023)
In order to investigate and evaluate the potential of CBM Resources in the southern margin of the Junggar Basin, this study conducted 3D seismic exploration in the Hutubi block. The seismic acquisition design tailors to wide azimuth, small receiver distance and high folds, the seismic geometry design includes 16 lines, 6 shots and 160 receivers. Given the serious static problems in mountainous terrain and imaging accuracy of steep dip coal seam in the seismic data processing, a high-resolution 3D seismic data processing flow is therefore established to meet the prediction requirement of coalbed methane enrichment area. The dividing principle of the coalbed methane enrichment area and the classification model of favorable area are proposed in line with the main seismic geological factors affecting coalbed methane enrichment, such as the coal seam depth, the faults characteristics, the coal seam thickness, the coal seam roof lithology and the coal seam gas content. Based on 3D seismic data, this study combined seismic data interpretation and seismic attribute analysis to obtain data on coal seam thickness, coal seam roof lithology, and coal seam gas content by using seismic lithology inversion results. Under the constraints of logging, this study made predictions of the B4 coalbed methane enrichment area in the research area, and put forward suggestions for deploying coal bed gas production borehole.